Di-tert-butyl N,N `-(octahydropentalene-2,5-diyl) dicarbamate - Kendhale, Amol M.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2008)
In the molecule of the title compound, C18H32N2O4, the central bicyclo[3.3.0] octane (octahydropentalene) has a rigid ring junction. Both rings of the bicyclo[3.3.0] octane unit adopt an envelope conformation, and the flexible tert-butylcarbamoyl side chains each have an extended conformation. Such a constrained bicyclo[3.3.0] octane aliphatic template is of interest with respect to the design of novel self-assembling motifs. Molecules related by c-glide symmetry are linked via intermolecular N-H center dot center dot center dot O hydrogen bonds, forming a two-dimensional layer structure. Neighboring layers are weakly associated along the a axis due to the close approach of the tert-butylcarbamoyl groups (2.55 angstrom).

Diversifying the structural architecture of synthetic oligomers: the hetero foldamer approach - Roy, Arup; Prabhakaran, Panchami; Baruah, Pranjal Kumar; Sanjayan, Gangadhar J. (Chemical Communications, 2011)
Conformationally ordered synthetic oligomers, also called ``foldamers'', have attracted considerable attention in recent years owing to their ability to mimic the structural architecture of biopolymers and also because of their potential applications in biomedical and material science fields. Until recently, the major focus in this area has been the development of oligomers featuring a single type of monomer building blocks. However, due to the enormous possibility of augmenting the conformational space available for oligomer design, the hetero foldamer approach has been introduced very recently. This feature article aims to describe foldamers with unique structural architectures, exclusively featuring heterogeneous backbones (hetero foldamers).

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.

Design and synthesis of 2-amino-thiophene-proline-conjugates and their anti-tubercular activity against mycobacterium tuberculosis H37Ra - Baravkar, Sachin B.; Wagh, Mahendra A.; Nawale, Laxman U.; Choudhari, Amit S.; Bhansali, Sujit; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
The emergence of extensively drug resistant tuberculosis (XDRTB) and multi-drug resistant tuberculosis (MDR-TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2-amino-thiophene-proline-conjugates which show potent invino and ex-vivo anti-tubercular (anti-TB) activity against mycobacterium tuberculosis (rntb) H37Ra. The synthesis of these 2-amino-thiophene-proline-conjugates was carried out via solution phase peptide coupling reactions using methyl-2aminothiophene-3-carboxylate 8 as an intermediate obtained by modified gewald reaction. Intermediate 8 was coupled with different amino acids to obtain dipeptides 3, 4, 5, 6a and 7. Priliminary anti-TB assay data encoureaged us to synthesize modified proline derivatives 6b-6k via formation of a benzoxazinone intermediate 16. Most of these conjugates are active against mtb H37Ra in both active (A) and dormant (D) strains. They are also active against drug resistant mtb H37Ra strains. A trifluoroethyl ester analog, 6i was the most potent among the series [MIC 1 mu g/mL] along with 6f and 6g [MIC 2-6 mu g/mL]. Cytotoxicity studies suggested that, these compounds are less cytotoxic to human cell lines HeLa, MCF-7, HUVEC and hence possess high selectivity index (SI). Docking studies revealed that the binding mode of most active compounds 6i, 6g and 6f is in accordance with their bioactivity studies having docking score 8.969, 8.446 and 7.865, respectively. More- over, in sllico ADME properties suggest that all the compounds possess drug like properties.
Keywords: 2-aminothiophene; Anti-tubercular; docking studies; Inh A gene; selectivity index

Dimedone-based rigid organic scaffold for organizing symmetrical helical peptide chains. - Madica, Krishnaprasad; Lakshmi, Jerripothula K.; Madhu, Suresh; Nadimpally, Krishna Chaitanya; Gonnade, Rajesh; Jagadeesh, Bharatam; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
We describe herein design, synthesis and conformational investigations of polypeptides attached on a rigid dimedone template. Two identical peptide chains are attached on a single carbon containing dimedone as a scaffold. Dimedone assists in controlling the secondary interactions through strong intramolecular helical C-12 and C-15 membered bifurcated hydrogen bonding on both the peptide chains along with propagating the helical architecture of the peptide chains attached. There exists a C-6 hydrogen bonding for the single stranded peptides attached to dimedone. Extensive structural investigations involving single crystal X-ray diffraction, solution-state NMR and CD studies of oligopeptides have been undertaken.
Keywords: dimedone; Helical; hydrogen bonding; Peptides; template

Discovery of SARS-CoV-2 inhibitors featuring novel histidine α-nitrile motif - Gone, Nilu Vijay; Enayathullah, Mohammed Ghalib; Thomas, Jessie; Rathee, Parth; Prabhakar, Rajeev; Bokara, Kiran Kumar; Sanjayan, Gangadhar J. (Chemistry and Biodiversity, 2023)
As COVID-19 infection caused severe public health concerns recently, the development of novel antivirals has become the need of the hour. Main protease (Mpro) has been an attractive target for antiviral drugs since it plays a vital role in polyprotein processing and virus maturation. Herein we report the discovery of a novel class of inhibitors against the SARS-CoV-2, bearing histidine alpha-nitrile motif embedded on a simple dipeptide framework. In-vitro and in-silico studies revealed that the histidine alpha-nitrile motif envisioned to target the Mpro contributes to the inhibitory activity. Among a series of dipeptides synthesized featuring this novel structural motif, some dipeptides displayed strong viral reduction (EC50=0.48 mu M) with a high selectivity index, SI>454.54. These compounds also exhibit strong binding energies in the range of -28.7 to -34.2 Kcal/mol. The simple dipeptide structural framework, amenable to quick structural variations, coupled with ease of synthesis from readily available commercial starting materials are the major attractive features of this novel class of SARS-CoV-2 inhibitors. The histidine alpha-nitrile dipeptides raise the hope of discovering potent drug candidates based on this motif to fight the dreaded SARS-CoV-2.
Keywords: dipeptide inhibitors; histidine alpha-nitrile; M-pro (main protease); molecular dynamics; SARS-CoV-2

Dynamic janus hydrogen bond mimicry unlocks tough, flexible supramolecular elastomers for strain sensing - Lakshmi, Durga; Wagh, Mahendra A.; Sharma, Aakash; Alam, Md Shafi; Selvan, T. Muthamil; Torris, Arun; Mondal, Titash; Sanjayan, Gangadhar J.; Nair, Kiran Sukumaran (Chemistry of Materials, 2026)
Flexible and wearable electronics demand stretchable sensors with polymer elastomers as key matrixes for mechanical flexibility and durability. However, despite their excellent elasticity, their limited mechanical strength remains a challenge. To address this limitation, in this study, we report the rational design of supramolecular polyurethane elastomers (SPUs) incorporating nucleobase-inspired aminopyrimidinedione with DDA-AAD (G-C mimic) reversible triple hydrogen bonds. This dual-domain architecture gives rise to a durable supramolecular network with enhanced mechanical properties, yielding elastomers that are soft, stretchable, and tough. By tuning of the density of dynamic cross-links, mechanical properties were systematically modulated. SPU-0.5 exhibited a maximum tensile strength of 16.14 MPa, representing a 67-fold strength enhancement over that of SPU-0. Although increasing the aminopyrimidinedione (APD) content reduced elongation, SPU-0.2 retained a high elongation of 1060% and showed the lowest residual strain during cyclic tests. To be of great interest, the activation energy increased with increasing hydrogen bonding content up to SPU-0.1, whereas beyond SPU-0.2 it decreased, likely due to extensive hydrogen bond formation. Furthermore, SPU-0.2-SP, a conductive variant, demonstrated a promising strain-sensing performance even after hundreds of cycles. Overall, the insights gained from this study advance the development of intelligent soft materials and lay the groundwork for next-generation flexible and wearable electronic devices.